2016
DOI: 10.1037/pst0000064
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of body image with symptoms of depression and anxiety in patients with anorexia nervosa during outpatient psychotherapy: Results of the ANTOP study.

Abstract: Body image disturbance represents a central characteristic of anorexia nervosa (AN). Depression and anxiety are the most common mental comorbidities in patients with AN. This study aims to investigate the relationship of body image with symptoms of depression and anxiety during outpatient psychotherapy in AN. Analyses were conducted using the data set of the Anorexia Nervosa Treatment Outpatient Study (ANTOP) randomized controlled trial. The ANTOP study included N = 242 females with AN between 18 and 56 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
1
8

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 51 publications
(84 reference statements)
2
31
1
8
Order By: Relevance
“…It might be understood in the sense that general anxiety symptoms are too broad to capture the more specific fears of patients with AN (fear of gaining weight, fear to eat) and hence may not detect adequately body‐related anxiety of patients with AN. Reflecting the results on our own recent work (Junne et al, ; Mölbert, Thaler, et al, ; Mölbert, Klein, et al, ), the here presented results underline the importance of cognitive–emotional body image perceptions for treatment outcomes in patients with AN.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…It might be understood in the sense that general anxiety symptoms are too broad to capture the more specific fears of patients with AN (fear of gaining weight, fear to eat) and hence may not detect adequately body‐related anxiety of patients with AN. Reflecting the results on our own recent work (Junne et al, ; Mölbert, Thaler, et al, ; Mölbert, Klein, et al, ), the here presented results underline the importance of cognitive–emotional body image perceptions for treatment outcomes in patients with AN.…”
Section: Discussionsupporting
confidence: 85%
“…However, it is unclear so far, what exact effects body image alterations might have on the complex interplay of disease modifying factors during AN treatment. In our recent work, we have shown that body image perceptions predict symptoms of depression and anxiety in the course of outpatient treatment in patients with AN (Junne et al, 2016). On the basis of the latter findings, we hypothesize that body image dimensions predict eating disorder relevant outcomes such as the body mass index (BMI) directly or via the determination of affective symptoms in patients with AN.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Recent reviews suggest that non‐visual body representations and the integration of different body representations might play a crucial role in the perceptual body image disturbance (Gaudio, Brooks, & Riva, ; Mölbert et al, ). However, discrepancies have also been observed in cognitive–affective measures of self‐body perception: women with AN usually report a high drive for thinness and high levels of body dissatisfaction but indicated satisfaction with their body weight or even a desire for weight gain in other studies (Boyd et al, ; Cash & Deagle, ; Junne et al, ; Striegel‐Moore et al, ). A synthesis of these heterogeneous observations that accounts for similarities and differences between the different assessment methods is still outstanding.…”
mentioning
confidence: 97%